2018
DOI: 10.1136/bjsports-2017-097853
|View full text |Cite
|
Sign up to set email alerts
|

What factors must be considered in ‘return to school’ following concussion and what strategies or accommodations should be followed? A systematic review

Abstract: ObjectiveTo evaluate the evidence regarding (1) factors affecting return to school (RTS) and (2) strategies/accommodations for RTS following a sport-related concussion (SRC) in children and adolescents.DesignA systematic review of original studies specifically addressing RTS following concussion in the paediatric and sporting context.Data sourcesMEDLINE (Ovid), Embase (Ovid), PsycInfo (Ovid) electronic databases and the grey literature OpenGrey, ClinicalTrials.gov and Google Advanced.Eligibility criteriaStudie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 61 publications
1
53
0
Order By: Relevance
“…Though no retrieved articles evaluated the effectiveness of school accommodations, four consensus documents provided recommendations for school accommodations 1 9 29 37. Their common goal was to increase student participation without exacerbating symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though no retrieved articles evaluated the effectiveness of school accommodations, four consensus documents provided recommendations for school accommodations 1 9 29 37. Their common goal was to increase student participation without exacerbating symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Their common goal was to increase student participation without exacerbating symptoms. Medical and school-based teams should collaborate to counsel the student regarding gradually increasing the duration and intensity of academic activities 29 37. Protocols to RTS need to be personalised based on the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,18 Our finding that adequate school accommodations were associated with improved school HRQOL in SRC patients provides support for providing SRC patients with return-to-learn programs that allow students to make a gradual return to school and help minimize cognitive-related symptoms. 20,32,33 Future studies are needed to address the added clinical value of incorporating patient-reported HRQOL outcome measures into the standardized management of patients with acute concussion and PCSS.…”
Section: Discussionmentioning
confidence: 99%
“…Given that being a student is the primary occupation of childhood through to young adulthood, an emphasis on returning to school should be a top priority for children and families, more so than return to sport (22, 23). However, to date the emphasis in post-concussion management has been on return to play and sports (20, 21).…”
Section: Introductionmentioning
confidence: 99%